Hubungan Reseptor Dopamin D1 di Cortex Prefrontalis Tikus (Rattus norvegicus) Dengan Memori Kerja Setelah Stress Kronik = The Relation of Dopamin D1 Receptor in Rat (Rattus norvegicus) Prefrontal Cortex with Working ... - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2005)
Abstrak Chronic stress can impairs the maintenance of a novel short term memory, i.e. working memory. The impairment working memory relate with dopaminergic system in Prefrontal Cortex (PFC),i.e. level of dopamin and its receptor D1 density. The aim of this research was to investigate: 1) the effect of chronic stress on working memory, and 2) relation between receptor Dl density and working memory. The rats were divided randomly into two groups (each group consisted of five rats). Then, each group was trained in eight radial arm maze. After trained, both group was tested in radial arm maze (12 days). Start in the 13rd day, the Treated group was treated with noise stress (100-105 db, 8 h/d, 25 days). Performance of working memory after treated was tested in maze for both groups (12 days). Next, all rats were killed by transcardial perfusion and the PFC regions were dissected. The tissues were treated with imunohisto chemistry procedure. Results showed that chronic stress induces decrease of working memory performance related to down regulation of D1 receptor in PFC. The change of dopaminergic system activity in the PFC induced by chronic stress was thought to express as a stress respon than an organic dysfunction. It was concluded that chronic stress could decrease working memory, and 2) there was correlation between working memory with D1 receptor density